Evaluating the Quality of Archival Learning Programs Using the CIPP Model: A Case Study at SMK Negeri 9 Semarang - Wardani, Nanda Tyas; Ismiyati, Ismiyati; Tusyanah, Tusyanah; Sholikah, Mar’atus; Ratnanintyas, Dyah Ayu; Abdillah, Zuhdan Kamal (FKIP Universitas Lampung, 2025)
Evaluating the Quality of Archival Learning Programs Using the CIPP Model: A Case Study at SMK Negeri 9 Semarang. Objective: This study seeks to examine the evaluation of learning in the independent curriculum by applying the context, input, process, and product models. The Office Management and Business Services expertise program at SMK Negeri 9 Semarang has a subject, namely the sub-element of archive storage procedures, which has used the independent curriculum. Therefore, the purpose of this study is to evaluate the learning program using the CIPP Model. Methods: This study used a qualitative method design with 11 informants consisting of 2 teachers and 9 students. Furthermore, a content analysis was conducted by analyzing the curriculum content based on the construction of the CIPP model. Findings: In terms of context, archiving is embodied in the elements of archive management and focuses on practice, archiving is important in the Office Management and Business Services skill program, and there is no E-Archive training. Input aspects, teachers prepare teaching modules, students prepare learning materials, learning facilities are not optimal, PBL and PjBL learning models. Process aspect, learning for 3 hours and found obstacles. Product aspect, students practiced archive storage simulation. Conclusion: This study concludes that the implementation of learning the sub-element of archive storage procedures based on the independent curriculum is quite good, so it recommends that further research be carried out in various aspects of education, continuous and comprehensive evaluation, and development of archival learning content. Keywords: learning evaluation, CIPP model, archives, independent curriculum.